Impact of deep pectoral myopathy in broiler chickens and correlation with zootechnical variables - Silva, Marco Antônio Pereira da; Mota , Sérgio Gonçalves; Silva, Wanderson Rodrigues da; Cappato, Leandro Pereira; Oliveira, Rodrigo Fortunato de; Costa, Adriano Carvalho; Gadêlha, Stefany Cristiny Ferreira da Silva (Food Science and Technology, 2025)
Deep pectoral myopathy (DPM) is a silent anomaly that affects broiler chickens, causing condemnation of chicken breast meat, thereby leading to financial losses for the food industry. In this context, this work aimed to evaluate DPM incidence in commercial birds and quantify its correlation with zootechnical variables of broiler chicken batches produced by a poultry processing industry. Data were subjected to exploratory analysis considering the effect of each factor, followed by analysis of variance, and when significant, Tukey’s multiple comparison test was performed. Data were also subjected to Pearson’s linear correlation and principal component analysis. It was found that the DPM incidence was 1.63%, representing a daily average loss of 2,523 kg of chicken breast meat. The distribution by classes allowed the identification of categories with higher incidence in the DPM, namely: season (autumn; 1.83%); average age (> 44 days; 2.06%); daily weight gain (> 64 g; 1.58–1.64%); and mortality (> 8.52%; 1.84%); for the variables average weight and slaughter density, no differences were observed (p < .05). Measuring the DPM impact in commercial birds and its correlation with zootechnical variables has practical relevance for the food industry as it allows for the directing of efforts towards establishing productivity goals aimed at reducing its incidence.